THE A-MODE SUTURAL ONTOGENY IN PROLECANITID AMMONOIDS - Korn D.; Ebbighausen V.; Bockwinkel Ju.; Klug Ch. (My University, 2003)
The generally accepted theory of a U-mode sutural ontogeny of prolecanitid ammonoids and their descendants is refuted. The basic suture formula of the order Prolecanitida is E A L U I (not E L U2 U1 I), resembling that of derived members of the suborder Tornoceratina (their phylogenetic ancestors), and of the suborder Goniatitina. During phylogeny of the prolecanitids, secondary umbilical lobes are introduced and lead to multilobate forms. In early ceratites, the original L lobe disappeared, and an increase in sutural elements took place by the introduction of supplementary U lobes. Consequently, sutural nomenclature of Permian ceratites and Mesozoic ammonoids has to be modified.
Keywords: CARBONIFEROUS; PERMIAN; MESOZOIC; SUTURAL ONTOGENY; AMMONOIDS; PROLECANITIDA; Paleozoic::Carboniferous; Палеозой::Каменноугольная